Physiological Conditions of Broiler Chickens During Transportation with Vitamin Treatment and Distance Difference - Dein Iftitah; Bayu Arisandi; RR Retno Widyani; Juniah (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
The physiological condition of broiler chickens during the transportation process has changed, presumably due to changes in environmental conditions. Changes in the environment, such as transport distance, density in the basket, vehicle speed and vibration, and heat stress during the transportation process, are thought to cause stress in chickens, disrupting the body's homeostatic and metabolic processes. The condition of stressed chickens harms the physiology of livestock, especially the biochemical components. It can result in decreased body weight, increased heart rate, respiration, and increased temperature, to the chickens' hematological status, which can be detrimental to breeders' income. Giving commercial vitamins containing vitamins A, D, E, K, B, and C, minerals, and amino acids is an alternative solution that can minimize stress levels in broiler chickens. This study aims to analyze the physiological condition of broiler chickens given vitamins and without vitamins with different mileage during transportation. The research method used was an experimental method using a randomized block design. This study used a sample of 48 broiler chickens with a weight range of 1.4 to 1.9 kg, treated with vitamins and without vitamins at a distance of 0 km (control), 30, 60, and 90 km. The parameters measured were heart rate, respiratory frequency, temperature, and body weight. Hematological tests measured were erythrocytes, hematocrit, hemoglobin, platelets, and leukocytes. The data were analyzed statistically. This research concludes that giving vitamins can stabilize the physiological condition of broiler chickens while being transported at a certain distance of 0 km (control), 30, 60, and 90 km. The treatment of giving vitamins at a distance of 90 km was no different from the control treatment. Evidenced by measurements of body weight with a value of 1.47 kg, heart rate of 262 times per minute, a stable respiratory rate at a value of 31 times per minute, and rectal temperature of 41 °C and hematological conditions of chicken blood such as erythrocytes of 2.60 c 106 mL, hematology 13.5 g/dL, hematocrit 33%, platelets 145 ´ 103 mL, and leukocytes 9 ´ 103 mL, are all in the normal range of broiler physiological conditions. Furthermore, it proves that giving vitamins can maintain the condition of the chicken's body from environmental temperature changes, transportation distance, transportation speed, and the density of transport baskets during transportation.